Morning Administration is More Effective than Evening Administration of 0.01% Atropine Eye Drops Combined with Orthokeratology for Myopia Control - Shuting Xiong; Xuewei Li; Yuchang Lu; Mengyao Zhang; Yan Li; Kai Wang (Indian Journal of Ophthalmology)
Objective: To assess the varying myopia control outcomes between morning (QM) and evening (QN) application of 0.01% atropine drops in conjunction with orthokeratology (ortho-K) therapy in myopic children. Methods: A total of 163 right eyes of myopic children were included, receiving either morning or evening 0.01% atropine combined with ortho-K, with 78 in the QM group. Age, gender, spherical equivalent refraction, axial length, e-value, average K-reading (Ave-K), and pupil diameter (PD) were all documented as baseline characteristics. Follow-up assessments at 1-, 3-, 6-, 9-, and 12-month visits were centered on alterations in treatment zone diameter (TZD), decentration, PD, and axial elongation. Parental refraction and children’s behavioral factors, such as daily near-work time, outdoor activity time, reading and writing posture, and sweets consumption, were gathered through a questionnaire. Results: At baseline, there were no significant differences in ocular characteristics between the two groups. After one month, the QM group exhibited a significantly larger PD compared to the QN group (4.09 ± 0.67 mm vs. 3.84 ± 0.76 mm, P = 0.03), while measurements for TZD and decentration showed no significant variance. Over the course of 1 year, the QM group demonstrated significantly less axial elongation than the QN group (0.13 ± 0.19 mm vs. 0.21 ± 0.16 mm, P < 0.05). Parental refraction and behavioral factors were similar between the groups, except for a lower consumption of sweets in the QM group. Regression analysis revealed that the timing of atropine administration, age, PD, and reading and writing posture were significant predictors of axial elongation over the 12-month period. Conclusion: Morning administration of 0.01% atropine eye drops combined with ortho-K shows greater efficacy in managing axial elongation than evening administration.